OFR-164-77 Conceptual Design And Engineering, Economic And Environmental Analysis Of Surface Pit Slope Caving Mining System - H. M. Coggin (The National Institute for Occupational Safety and Health (NIOSH), 1977)
The study summarizes the state of the art in rock mechanics, open pit and underground mining, leaching, geology, metallurgy and financial analysis Conceptual design of pit slope caving technique and analyses explore concepts for the exploitation of ore grade remnants in the walls and bottoms of open pit mines and the potential economics of the adaptations Several coded sites were examined for future studies where the feasibility of the method may be demonstrated. An extensive bibliography has been developed